Same setup as before. Just assign a variable to the smallest and then make the larger a function of the smallest by adding 2 to each.

x is the smallest odd integer

x + 2 is the next

x + 4 will be the third.

Sum of the smallest and four times the largest is 61, so that is our equation;

x + 4(x+4) = 61

x + 4x + 16 = 61

5x = 45

x = 9

so the next will be 11, and the next 13

But let's check it to be sure;

(I caught my own error checking it this way)

9 + 4 (13) = 61

So it checks

x is the smallest odd integer

x + 2 is the next

x + 4 will be the third.

Sum of the smallest and four times the largest is 61, so that is our equation;

x + 4(x+4) = 61

x + 4x + 16 = 61

5x = 45

x = 9

so the next will be 11, and the next 13

But let's check it to be sure;

(I caught my own error checking it this way)

9 + 4 (13) = 61

So it checks